Application of Pulsed eddy current technique to stress and residual stress measurement - Abbas Habibalahi; M. S. Safizadeh (International Journal of Advanced Design and Manufacturing Technology, 2014)
Stress and residual stress are the main problems in the operating performance of materials. They are the principal causes of material failure and can affect life time of component. However measurement or predictions of them are typically difficult. Two common non-destructive methods, X-ray diffraction and ultrasound are not reliable methods for subsurface residual stress measurements and destructive hole-drilling method is not absolutely precise and safe. In this study, the PEC method was applied to the qualitative and quantitative measurements of stress in aluminum alloy specimens. PEC is a high performance non-destructive testing technique but its application in stress and residual measurement is unknown. In this study a qualitative and quantitative approach for measuring residual stress by PEC technique was developed. Results indicated that pulsed eddy current responses are sensitive to stress and showed PEC method is capable of residual stress measurements.